النظام القانوني للمسجد في التشريع الجزائري - فاطمة الزهرة، غيلاني; مسعودة ،فطحيزة علي; مليكة، العانز (جامعة الوادي University of El Oued, 2024)
تتميز المؤسسة المسجدية بطابع خاص، باعتبارها من الأوقاف العامة من جهة، وأنها مؤسسة ذات طابع قانوني تعبدي من جهة أخرى؛ مكلفة قانونا بتقديم خدمة عمومية وشرعا بترقية قيم الدين الإسلامي في المجتمع وفقا لمبادئ الشريعة الإسلامية. ولا يمكن لهذه المؤسسة أن تؤدي دورها ونشاطها بفعالية وديمومة إلا في ظل إطار مؤسسي يضمن حماية رسالتها ووظائفها من جهة، ويطور إمكاناتها المالية والبشرية وفق آليات أكثر مرونة من جهة أخرى. ومن ثمّ وجب استغلال موارد هذه المؤسسة البشرية منها والمالية لتحقيق الأهداف المنوطة بها شرعا وقانونا، وهذا في إطار فتح مجالات مشتركة تجمع الهيئات الإدارية والمجتمعية وفق نصوص قانونية تنظم هذه المجالات . هذا كله تطلب وجود منظومة قانونية محكمة تضبط إقامة المساجد وتُنظم نشاطها وتضمن لها الحماية القانونية وتعكس استقلاليتها وتدعمها في أداء رسالتها الدينية والمجتمعية. The mosque institution is distinguished by its unique nature, functioning as a public endowment on one hand and as a legal religious entity on the other. Legally mandated to provide public services, it is also religiously obligated to promote the values of Islam in society according to the principles of Islamic Sharia. For this institution to effectively and sustainably fulfill its role and activities, it must operate within an institutional framework that both protects its mission and functions and enhances its financial and human resources through more flexible mechanisms. Therefore, it is essential to utilize the institution's resources, both human and financial, to achieve its legally and religiously mandated objectives. This requires establishing joint fields that connect administrative and societal bodies through legal provisions that regulate these areas. All of this necessitates a robust legal system that governs the establishment of mosques, organizes their activities, ensures their legal protection, reflects their independence, and supports them in fulfilling their religious and societal missions
ماستر اداري